2018
DOI: 10.1590/s0004-2803.201800000-26
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Anxiety and Depression, and Quality of Life of Patients With Crohn’s Disease

Abstract: -Background -Crohn's disease is an idiopathic chronic inflammatory disease. It is classified as an inflammatory bowel disease. Crohn's disease can change patient quality of life, especially during flares. Crohn's disease has been associated with symptoms of anxiety and depression, because the clinical symptoms have a high impact on quality of life. Objective -To investigate the prevalence of symptoms of anxiety and depression in Brazilian patients diagnosed with Crohn's disease, as well as their quality of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
2
12
0
4
Order By: Relevance
“…The mean and standard deviation of the age of the participants in the present study was 31 ± 7.79, similar to other fi ndings in the literature, with mean ages of 21.2 years [6], 33 years [7] and 37.5 years [15]. Regarding marital status, the other studies [5,13,14] found that married people adhered better to treatment, representing at least 66% of the population, which is close to the result obtained herein.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The mean and standard deviation of the age of the participants in the present study was 31 ± 7.79, similar to other fi ndings in the literature, with mean ages of 21.2 years [6], 33 years [7] and 37.5 years [15]. Regarding marital status, the other studies [5,13,14] found that married people adhered better to treatment, representing at least 66% of the population, which is close to the result obtained herein.…”
Section: Discussionsupporting
confidence: 90%
“…The same peculiarity was described in the study by [11], who obtained similar results regarding the proportion of female individuals in their research, being three times higher when compared to the number of male individuals. Other studies [5,7,[12][13][14] also reported a greater participation of women in the analysis (> 50%). This is due to a greater concern with health and a greater endency to participate in health-related research that women mostly present [6], when carrying out a survey with 532 individuals diagnosed with CU, reported that 74.62% (n = 397) declared themselves to be white, similar to the present study.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…IBD have a bimodal characteristic, with incidence in young adults and later in those over 50 years of age. The results of the study showed higher incidence in females (73.2%), CD diagnosis (63%), and an average age of patients 46.5 years, slightly above when compared with some studies (1)(2)(3)(4)(5)(6)(7)(8)(9) and the regional study of scores. These significant findings allow to establish the correlation between the two methods analyzed, being good indicators of QOL in patients with IBD.…”
Section: Discussionmentioning
confidence: 45%
“…Symptoms such as depressive mood, anxiety and irritability have a high impact on QOL and, according to Teixeira et al (11) , they may emerge as a response to real situations when faced with unpleasant facts. Benvegnú and Tomazoni (9) state that such symptomatology reflects psychological distress, and may exacerbate against the greater activity of the disease.…”
Section: Resultsmentioning
confidence: 99%